1980
DOI: 10.1180/minmag.1980.043.331.06
|View full text |Cite
|
Sign up to set email alerts
|

Clay mineral evidence for low-grade Caledonian and Variscan metamorphism in south-western Dyfed, south Wales

Abstract: SummaryIllite crystallinity determinations on Palaeozoic pelitic rocks, whose stratigraphic range runs from Lower Cambrian to Westphalian, indicate that anchimetamorphism has affected both the Lower and Upper Palaeozoic sequences. Two metamorphic episodes are in evidence, with the earlier, Caledonian, being of slightly higher grade. The higher anchizone crystallinity values are recorded from the Fishguard area in which mineral assemblages of the prehnite-pumpellyite facies have recently been recognized in basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…1980). Nevertheless, there has been an increasing interest in the metamorphic character of the region, with Bevins (1978) describing prehnite-pumpellyite assemblages in metabasites from the Fishguard Volcanic Complex of North Pembrokeshire and Robinson, Nicholls & Thomas (1980) identifying both Caledonian and Variscan metamorphic events in south-west Wales using clay mineral and illite crystallinity data. Subsequent regional surveys have been undertaken which utilize metabasite assemblages (Roberts, 1981;Bevins & Rowbotham, 1983) and illite crystallinity (Cronshaw, 1985;, whilst additional data have also become available which are based on conodont colour index (CAI) determinations (Bergstrom, 1980;Savage & Bassett, 1985;Aldridge, in press) and graptolite reflectance studies (Oliver, in press).…”
Section: Introductionmentioning
confidence: 99%
“…1980). Nevertheless, there has been an increasing interest in the metamorphic character of the region, with Bevins (1978) describing prehnite-pumpellyite assemblages in metabasites from the Fishguard Volcanic Complex of North Pembrokeshire and Robinson, Nicholls & Thomas (1980) identifying both Caledonian and Variscan metamorphic events in south-west Wales using clay mineral and illite crystallinity data. Subsequent regional surveys have been undertaken which utilize metabasite assemblages (Roberts, 1981;Bevins & Rowbotham, 1983) and illite crystallinity (Cronshaw, 1985;, whilst additional data have also become available which are based on conodont colour index (CAI) determinations (Bergstrom, 1980;Savage & Bassett, 1985;Aldridge, in press) and graptolite reflectance studies (Oliver, in press).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that illite crystallinity increases with metamorphic grade; as the grade increases, illite becomes more ordered, and accordingly the shape of the illite (001) peak becomes sharper and the peak:background ratio increases. Robinson et al (1980) examined illites from Lower Palaeozoic pelites of southwest Dyfed, and concluded that they represented illites of anchizone metamorphism. Therefore they agree with the indication of prehnite-pumpellyite facies metamorphism in metabasites as reported here (if the correlation of Kisch (1974) is followed), and earlier by Bevins (1978).…”
Section: Comparison With Other Low-grade Metamorphic Indicatorsmentioning
confidence: 99%
“…It has commonly been referred to as being unmetamorphosed, or as belonging to 'the non-metamorphic Caledonides' (Kelling 1978;Anderson and Owen 1980;Soper 1980). However, in the past few years, a number of workers (Bevins 1978;Oliver 1978;Robinson et al 1980;Oliver and Leggett 1980;Roberts 1981;Bevins et al 1981) have shown that parts of the paratectonic Caledonides have been metamorphosed within the prehnite-pumpellyite facies and lower part of the greenschist facies.…”
Section: Introductionmentioning
confidence: 99%
“…White mica crystallinity has been widely used to calibrate the low-grade metamorphism of rocks in the Welsh Basin (Robinson et al, 1980;Roberts & Merriman, 1985;Robinson & Bevins, 1986;Mackie, 1987;Pratt, 1990). However, there is disagreement regarding the factors that controlled crystallinity variation in Wales.…”
Section: Introductionmentioning
confidence: 99%